Analysis of North‐American Tight oil production. Issue 4 (30th November 2017) - Velasco, Raul; Panja, Palash; Pathak, Manas; Deo, Milind
Abstract : North‐American tight oil production has been on the rise due to the introduction of new drilling and hydraulic fracturing technologies. Such advances have dramatically changed the conventional understanding of the hydrocarbon recovery process. A dimensionless study of tight oil production across the United Sates in plays such as the Bakken, Niobrara, Eagle Ford, Woodford, Bone Spring, and Wolfcamp shed light on some of these recovery processes. Production from any well, regardless of geologic attributes and operating conditions, fits into a universal curve during its initial productive period. Subsequently, production becomes a strong function of hydrocarbon thermodynamics and multiphase flow. Results from this analysis help rank important parameters that affect oil recovery in terms of how wells are operated and the reservoir's intrinsic geological and fluid properties. Furthermore, production results are combined with a simple dimensionless economic analysis to determine optimal fracture configurations independent of oil price environment. © 2017 American Institute of Chemical Engineers AIChE J, 64: 1479–1484, 2018